PENGARUH TATA KELOLA PEMERINTAHAN, EFEKTIVITAS PENGENDALIAN INTERNAL, DAN PERAN AUDITOR INTERNAL TERHADAP TINGKAT KECURANGAN (Studi Pada SKPD Kota Bukittinggi) - Karlina Gita Oktavia; Andreas Andreas; Susilatri Susilatri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of good governance, internal control effectiveness and the role of the internal auditor on the level of fraud. The study was conducted using a survey method. The population in this study were 29 government agencies in the city of Bukittinggi. Samples taken are 87 respondents. Data analysis methods are used alternately regression (multiple regression) with SPSS Version, 17.0. The results of this study indicated that the role of the internal auditor affect the level of fraud, but the good governance and internal control effectiveness don’t affect the level of fraud. The magnitude of the effect adjusted R2 of good governance, internal control effectiveness, and the role of the auditor on the level of fraud was 9,7%. The remaining 90,3% is influenced by other variables.Keywords: good governance, internal control effectiveness, internal auditor, and the level of fraud.